COMPLEMENTARY THERAPIES FOR LABOR INDUCTION AND THEIR LEGALITY IN INDONESIA: A LITERATURE REVIEW - Dwi Hesti Diah Citrawati; Listyaning Eko Martanti (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Labor induction is performed using two methods of pharmaceuticals and complementary therapies. The complementary therapies for labor induction in particular, have to be reviewed comprehensively as to come up with the most relevant therapies allowed to be performed by midwives in Indonesia in accordance with the applicable law. This study aimed to identify the effectiveness and safety of complementary therapies for labor induction that can be performed and also allowed by the applicable law. Method: This was a literature review based on the PRISMA protocol guidelines. The full-text articles were obtained from several databases, such as Elsevier, Cochrane, PubMed, and local journals.  These chosen articles were then reviewed to figure out the most effective interventions for labor induction. They were then further reviewed for compatibility with applicable midwifery law.Results: Out of 1153 studies obtained, 44 studies were included in this review. The most effective complementary therapies for labor induction are acupuncture and acupressure. The current law does not allow midwives to perform acupuncture, but it states that acupressure can be administered. Acupressure has proven to be a successful intervention when it is coupled with aromatherapy or hypnobirthing. Conclusion: Considering the effectiveness and safety of complementary therapies for labor induction, acupressure along with aromatherapy or hypnobirthing can be used after being administered in accordance with the applicable law. There is a need for further studies focusing on either the holistic therapy alternatives or the legal side of holistic therapy.